METHODS OF TEACHING GRAMMAR THROUGH HOMEWORK - Rustamov, Ilxom; Ataboyev Isroiljon Mirza o`g`li, (Журнал иностранных языков и лингвистики, 2023)
This article looks at the basics and the important role of teaching grammar through assignments